Độ dày lớp xáo trộn bề mặt và độ ổn định thẳng đứng của nước biển trên thềm lục địa nam Việt Nam - Lanh, Vo Van; Sam, Tran Van; Dung, Nguyen Tien; Bien, Nguyen The; Hoa, Nguyen Kim (Vietnam Journal of Mechanics, 1986)
None